INNOVATIVE LAND TENURE IN THE PERIOD OF LAND REFORM - Kolganova, I. G. (Land Management, Cadastre and Land Monitoring, 2012)
Tendencies of development of documentation on land management in carrying out land reform in Ukraine are shined. It is proved thst the man problem in implementation of survey works is absence of innovative land management documentation, in particular land planning documentation, and projects of the organization of the territory.